2016
DOI: 10.1177/0748730416655929
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Time Keeping in a Long-Distance Migrating Shorebird

Abstract: Because of the complications in achieving the necessary long-term observations and experiments, the nature and adaptive value of seasonal time-keeping mechanisms in long-lived organisms remain understudied. Here we present the results of a 20-year-long study of the repeated seasonal changes in body mass, plumage state, and primary molt of 45 captive red knots Calidris canutus islandica, a High Arctic breeding shorebird that spends the nonbreeding season in temperate coastal areas. Birds kept outdoors and exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 60 publications
1
39
0
Order By: Relevance
“…return to roost) [55,152], and the timing of one activity may be more important than that of others. A recent study of waders found that different aspects of their annual cycle were varying in ways suggestive of process-specific chronotypes, making it difficult to define the most appropriate descriptor [16,153]. Furthermore, plasticity of chronotype to environmental factors, as described above, can complicate analyses, especially if repeated measurements are not feasible (e.g.…”
Section: (B) Chronotypementioning
confidence: 99%
See 1 more Smart Citation
“…return to roost) [55,152], and the timing of one activity may be more important than that of others. A recent study of waders found that different aspects of their annual cycle were varying in ways suggestive of process-specific chronotypes, making it difficult to define the most appropriate descriptor [16,153]. Furthermore, plasticity of chronotype to environmental factors, as described above, can complicate analyses, especially if repeated measurements are not feasible (e.g.…”
Section: (B) Chronotypementioning
confidence: 99%
“…As an example of species-specific effects, migratory species that utilize seasonal resources at sequential sites over the course of the year now have to cope with strongly diverging changes in phenology at the various sites. They will have to adjust multiple components of their annual cycles, putting multiple selection pressures on the integrated chronotypes [153]. On the level of species interactions, a potential powder barrel are changes in host-parasite relationships, if for example parasites and vectors can extend their annual temporal niches and expand into regions that no longer show prohibitive seasonal changes [23,103].…”
Section: Outlook: Wild Clock Research Across Levels Of Biological Orgmentioning
confidence: 99%
“…As the birds approach the breeding grounds, environmental cues will become progressively more 14 . In contrast, the post-breeding life-cycle stages of red knots drifted more swiftly toward later dates (i.e.…”
Section: Key Questions: Are Life-cycle Stages Independently Modified mentioning
confidence: 99%
“…These observations prompted Kramer 8 to propose that the integration of an inherited sense of time with an inherited sense of direction could function as a "clock and compass" mechanism, which could guide inexperienced birds on their first journey before learning about the environment en route. Since then, captive studies of a wide range of migratory species, and systematic experimentation of the captive environment have identified detailed time programs and their interactions with selected environmental factors 4,10,13,14,16 . Many of the sophisticated adaptations of migratory programs can best be studied in individually migrating songbird species, especially in hand-raised individuals during their first journey when young birds are still naïve.…”
Section: Introductionmentioning
confidence: 99%
“…The data included circannual periods for all available life cycle stages. However, circannual‐period lengths often change in the course of cue‐deprived treatments (Gwinner, ; Karagicheva, Rakhimberdiev, et al., ), and most of the circannual‐period lengths were available for the first one or two years spent under experimental conditions. We therefore limited our sample to transitory cycles during which the animals were transferred from natural to constant photoperiods (cycle 0), and the first cycle (cycle 1) when animals were exposed to a constant photoregime the whole year (Table ).…”
Section: Methodsmentioning
confidence: 99%